A revisit to the separation of a binary mixture of ethanol–water using ultrasonic distillation as a separation process - Spotar, Sergey; Rahman, Asad; Gee, Ooi Chel; Jun, Kon Kee; Manickam, Sivakumar (Chemical Engineering and Processing: Process Intensification, 2015)
Abstract Ethanol separation from binary ethanol–water mixture by utilizing “ultrasonic atomization” or ‘ultrasonic distillation’ has been investigated and inferred as a case of evaporation. It was assumed that the operation of ultrasonic transducer reveals itself as mechanical agitation where the ultrasonic energy is ultimately regarded as heat input into the separation unit. Thus the local deviations from non-equilibrium owing to the propagation of ultrasonic waves through the bulk liquid were excluded from consideration. The process is accompanied by an enlargement of total vapor–liquid interfacial area due to the generation of atomized mist droplets that are supposed to have the same composition as that of bulk liquid. It contradicts with the previous concept of ‘ultrasonic distillation’ where the mist droplets were characterized by a higher percentage of volatile (ethanol) fraction. Consequently, this study demonstrates that ethanol enrichment process reported earlier might still be assessed by assuming that initial mist droplets have the same composition as that of the bulk liquid mixture. Thus, either by ultrasonic distillation or by bubbling carrier gas through the bulk liquid or even blowing it over the surface of the liquid, the conversion of liquid into vapour phase occurs and could be interpreted as equivalent to evaporation phenomena.
Keywords: Distillation; Ultrasound; Cavitation; Separation; Aeration; Diffusion; Interface; Evaporation